Persepsi Minat Mahasiswa S1 Akuntansi Terhadap Karir Di Bidang Akuntansi Pemerintahan: - Sharly Ramayani; Vita Fitria Sari (Universitas Negeri Padang, 2019)
This reseacrh aims to examine the perception of interest from students towards a career in government accounting. The population in this research are students that year of entry is 2016 and 2015 from UNP and UNAND. The total sample was 310 students. The data used is primary data. The technique of collecting data by questionnaires. The analytical method used is descriptive analysis, inductive analysis and different test analysis. The result showed a 2-tailed significance value is 0,449 > 0,05. There is no significant difference between students before and after taking government accounting courses but career in government is quite attractive